Peningkatan keterampilan menulis karangan narasi melalui model pembelajaran kooperatif tipe scramble kelas III sekolah dasar - Selfiana Coo; Retno Winarni; Yulianti Yulianti (Didaktika Dwija Indria, 2019)
The purpose of this study is to improve writing skills through learning scramble cooperative type  in Grade III stundentsof  Laweyan  Primary School No.54 Surakarta Academic Year 2018/2019. The subject of this research were on classroom include teacher 35 students. The use of data were collected through observation, interview, tes and documention techniquers. The analysis data consist ofcollection data, reduction data, presentation data, and tge canclusions. The results of this study  is indicate that in the  acquisition value of the average narrative  writing essay skills are 56.51 with a 8.57% classical completeness. In the first cycle, the average score increased to 65.47 with a classical  completeness of 48.57%, while in the second cycle the average score was 74.82 with a 88.57% classical completeness. Based on the results of the research obtained, it shows that  learning model scramble cooperative type  can improve the narrative essay writing skills in grade III students of Laweyan No. SD Negeri. 54 Surakarta  Academic Year 2018/2019.